Building the African Union : an assessment of past progress and future prospects for the African Union's institutional architecture - Laporte, Geert (ECDPM MaastrichtNL, 2010)
Comprises a collection of papers presented by African and European policy-makers and researchers at an informal, high-level seminar held in 2009. Takes stock of the key challenges facing the AU and analyses its track record since 2002. Focuses on the AU's role in promoting African integration, the progress made in the last few years and the ongoing reforms that are designed to strengthen the AU institutions.